SCOPE AND FORMS OF AESTHETIC EDUCATION OF STUDENTS IN THE SYSTEM OF OUT-OF-SCHOOL EDUCATION INSTITUTIONS OF UKRAINE - Varnavska, Larisa; Viktorova, Margarita; Serhieieva, Viktoria (Sworld-Us Conference proceedings, 2023)
The work looks into the issue of aesthetic education of students in the system of out-of-school education institutions of Ukraine. The out-of-school education in Ukraine is an extensive network of institutions that work with children and youth in their fr